CYP94-mediated jasmonoyl-isoleucine hormone oxidation shapes jasmonate profiles and attenuates defence responses to Botrytis cinerea infection - Aubert, Yann (J Exp Bot, 2015)
Induced resistance to the necrotrophic pathogen Botrytis cinerea depends on jasmonate metabolism and signalling in Arabidopsis. We have presented here extensive jasmonate profiling in this pathosystem and investigated the impact of the recently reported jasmonoyl-isoleucine (JA-Ile) catabolic pathway mediated by cytochrome P450 (CYP94) enzymes. Using a series of mutant and overexpressing (OE) plant lines, we showed that CYP94B3 and CYP94C1 are integral components of the fungus-induced jasmonate metabolic pathway and control the abundance of oxidized conjugated but also some unconjugated derivatives, such as sulfated 12-HSO(4)-JA. Despite causing JA-Ile overaccumulation due to impaired oxidation, CYP94 deficiency had negligible impacts on resistance, associated with enhanced JAZ repressor transcript levels. In contrast, plants overexpressing (OE) CYP94B3 or CYP94C1 were enriched in 12-OH-JA-Ile or 12-COOH-JA-Ile respectively. This shift towards oxidized JA-Ile derivatives was concomitant with strongly impaired defence gene induction and reduced disease resistance. CYP94B3-OE, but unexpectedly not CYP94C1-OE, plants displayed reduced JA-Ile levels compared with the wild type, suggesting that increased susceptibility in CYP94C1-OE plants may result from changes in the hormone oxidation ratio rather than absolute changes in JA-Ile levels. Consistently, while feeding JA-Ile to seedlings triggered strong induction of JA pathway genes, induction was largely reduced or abolished after feeding with the CYP94 products 12-OH-JA-Ile and 12-COOH-JA-Ile, respectively. This trend paralleled in vitro pull-down assays where 12-COOH-JA-Ile was unable to promote COI1–JAZ9 co-receptor assembly. Our results highlight the dual function of CYP94B3/C1 in antimicrobial defence: by controlling hormone oxidation status for signal attenuation, these enzymes also define JA-Ile as a metabolic hub directing jasmonate profile complexity.